Understanding decentralization theory, evidence and method, with a focus on least-developed countries - Jean-Paul Faguet (London School of Economics and Political Science (LSE), Department of International Development, 2021)
What is decentralization, what is its underpinning rationale, and why might it matter for least-developed countries? This chapter has two goals: (i) to distill the enormous academic and policy literature on international experiences of decentralization into clear empirical conclusions; and (ii) to derive policy lessons relevant to least-developed countries. It first reviews the different definitions of decentralization employed in the literature before proposing one best suited to countries with the lowest levels of development. It reviews the most important theoretical arguments in favour of decentralization in low-income nations with low levels of human development that are often ethnically and religiously diverse. It then reviews empirical evidence on decentralization's ability to overcome some of the key obstacles holding back such countries' development, before concluding with key questions still to be answered, for which additional research is required.
Keywords: H41; H75; H77; O1; 330; decentralization; local government; democracy; accountability; civil conflict; least-developed countries